2017
DOI: 10.3892/etm.2017.5599
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid exerts cardioprotective effects in a rat model of acute myocardial infarction through inhibition of inflammation, iNOS and NF‑κB/p38 pathway

Abstract: Abstract. Gamboge, the dried resin secreted by Garcinia maingayii (gambogic tree), was previously demonstrated to exert anti-inflammatory effects. The present study examined the effects of gambogic acid, the major active constituent of gamboge, on myocardial infarction (MI) and inflammation in a rat model and explored the possible underlying mechanisms. The results demonstrated that gambogic acid inhibited the ratio of heart weight to body weight and myocardial damage (via lactate dehydrogenase and cardiac tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…p38 has also been linked to cardiac inflammation through its promotion of the expression of regenerating islet-derived 3γ (Reg3γ), a protein associated with cardiac inflammatory signaling [ 70 ]. Moreover, treatment with the anti-inflammatory compound gamboge protects against infarction-induced inflammation by targeting the NF-κB–p38 pathway [ 71 ]. p38α activation is also associated with increased fibrosis during ischemia-induced cardiac remodeling [ 72 ].…”
Section: P38 In Ischemia–reperfusion Injurymentioning
confidence: 99%
“…p38 has also been linked to cardiac inflammation through its promotion of the expression of regenerating islet-derived 3γ (Reg3γ), a protein associated with cardiac inflammatory signaling [ 70 ]. Moreover, treatment with the anti-inflammatory compound gamboge protects against infarction-induced inflammation by targeting the NF-κB–p38 pathway [ 71 ]. p38α activation is also associated with increased fibrosis during ischemia-induced cardiac remodeling [ 72 ].…”
Section: P38 In Ischemia–reperfusion Injurymentioning
confidence: 99%
“…Gambogic acid (GA), one of the major active ingredients extracted from Chinese medicine gamboges resin, is reported to possess antioxidant, antiinflammatory, and widespread anticancer activities with acceptable side effects (Na, Aijie, Bo, Zhilin, & Long, ; Wei et al, ; Yang & Chen, ). GA is capable of suppressing the growth of a variety of different tumors, such as lung, liver, and prostate cancers (Gu et al, ; Lu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial apoptosis induced by AMI may be related to the activation or inhibition of signaling pathways. Na et al has demonstrated that gambogic acid protects against myocardial damage in MI rats by activating NF-κB and p38 pathways [ 16 ]. Liu et al have found that inhibition of AMPK aggravated cell injury in OGD-mediated cardiomyocytes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%